2015
DOI: 10.1093/poq/nfv047
|View full text |Cite
|
Sign up to set email alerts
|

Sticker Shock

Abstract: This study examines the role of information in shaping public opinion in the context of support for education spending. While there is broad public support for increasing government funding for public schools, Americans tend to underestimate what is currently spent. We embed a series of experiments in a nationally representative survey administered in 2012 ( = 2,993) to examine whether informing citizens about current levels of education spending alters public opinion about whether funding should increase. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…Here we conducted another information experiment; a random half of respondents were informed of the average annual per pupil spending on public schools. All respondents were then asked whether taxes to support public schools should be increased or decreased on five-point scale (for a similar experiment, see Schueler and West 2016). In this study, respondents were randomized into either the post-only, pretest, or quasi design.…”
Section: Study 3-education Spending Information Experimentsmentioning
confidence: 99%
“…Here we conducted another information experiment; a random half of respondents were informed of the average annual per pupil spending on public schools. All respondents were then asked whether taxes to support public schools should be increased or decreased on five-point scale (for a similar experiment, see Schueler and West 2016). In this study, respondents were randomized into either the post-only, pretest, or quasi design.…”
Section: Study 3-education Spending Information Experimentsmentioning
confidence: 99%
“…For the substantive manipulation, a random half of respondents were informed of the average annual per pupil spending on public schools. All respondents were then asked if taxes to support public schools should be increased or decreased (for a similar experiment, see Schueler and West 2016). In this study, respondents were randomized into either the posttest, pretest, or quasi design.…”
Section: Study 3 -Education Spending Information Experimentsmentioning
confidence: 99%
“…In 2015, the year before the OSD ballot initiative, 11 states debated or passed legislation to create state turnaround districts (Layton, 2016). Schueler and West (2019) also found robust support for state takeover in a 2017 nationally representative survey.…”
Section: State Takeover In Georgiamentioning
confidence: 87%
“…Prior studies have highlighted how communities resist state takeover initiatives and the key players in the resistance in Memphis, Newark, Georgia, and New Orleans (Buras, 2013; Danley & Rubin, 2020; Dixson et al, 2015; Glazer & Egan, 2016, 2018; Morel, 2018; Russakoff, 2015; Welsh et al, 2019b). Race has played a prominent role in these studies, and other studies have focused explicitly on how support for state takeover varies across racial groups (Burns, 2010; Schueler & West, 2019; Wong & Shen, 2002). Burns (2010) examined race and the support for state takeovers and found that opposition to state takeover is driven by areas with a significant concentration of African American voters and high voter turnout among these voters.…”
Section: State Takeover In Georgiamentioning
confidence: 99%
See 1 more Smart Citation